2020
DOI: 10.1136/bmjopen-2019-036040
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group and the risk of aortic disease: a nationwide cohort study

Abstract: ObjectivesTo analyse the association between ABO blood group and aortic disease using data on blood donors and transfused patients from Sweden.DesignThis was a retrospective study using data from the Swedish portion of the Scandinavian Donations and Transfusions Database. The association between ABO blood group and aortic disease was analysed using log-linear Poisson regression models and presented as incidence rate ratios (IRRs).SettingSwedish population-based study.ParticipantsThe study cohort consisted of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It is reported that patients with B blood group are less likely to develop pancreatic neuroendocrine tumors and other types of pancreatic masses in Chinese population [11]. Meanwhile, a nationwide cohort study suggested that B blood group conferred a lower risk of aortic aneurysms when compared with O blood group [12]. Individuals with B blood group account for approximately 25% of Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that patients with B blood group are less likely to develop pancreatic neuroendocrine tumors and other types of pancreatic masses in Chinese population [11]. Meanwhile, a nationwide cohort study suggested that B blood group conferred a lower risk of aortic aneurysms when compared with O blood group [12]. Individuals with B blood group account for approximately 25% of Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that patients with the blood group B are less likely to develop pancreatic neuroendocrine tumors and other pancreatic masses in the Chinese population 11 . Meanwhile, a nationwide cohort study suggested that blood group B conferred a lower risk of aortic aneurysms than the blood group O 12 . A meta-analysis including 241.868 Hepatitis B virus (HBV)-infected subjects and 6.487.481 uninfected subjects also found that blood group B was associated with a lower risk of HBV infection (RR=0.92, 95% CI 0.86 to 0.98) 13 .…”
Section: Introductionmentioning
confidence: 99%